RECENT ADVANCES IN PHOTOCATALYTIC HYDROGEN GENERATION - Dutta, B.K. (Nova Science Publishers, Inc., 2011)
Photocatalytic splitting of water is a potentially important route of hydrogen generation utilizing solar energy. Starting in the early seventies with semi-conductor materials such as CdS and TiO2, the technique has undergone rapid development during the last fifteen years. Although many semi-conductors function effectively under UV radiation, photocatalytic action under solar or visible light illumination is essential for practical viability. Now a much wider range of catalysts and modified catalysts such as those based on tungsten, lanthanum, tantalum, niobium, gallium, etc., have been tested. Techniques of modification such as doping by another metal, addition of electron donors or suppressants of electron-hole recombination, noble metal loading, anion doping and ion implantation have shown promise to varying extents. The major technological challenges of practical application of the technique are to reduce the band-gap of the catalysts to bring them down to the energy range of visible light, to reduce recombination of the electrons and the holes that form upon irradiation, to prevent the reverse reaction of the products of photo-splitting, namely hydrogen and oxygen and eliminate sacrificial agents. Other challenges include reactor design for operating the process at a bigger scale and to make it economically competitive. In this chapter, we will make an attempt to review the recent developments in the above directions and also on characterization of the catalyst and the theoretical basis of catalyst design for commercial viability.